Economic growth determinants in new and old EU countries with focus on construction - Žarković, Miloš; Ćetković, Jasmina; Redzepagic, Srdjan; Đurović, Gordana; Vujadinović, Radoje; Živković, Angelina (Technological and Economic Development of Economy, 2022)
Classical, neoclassical, institutional and other schools have debated what is crucial for economic growth. Literature review related to economic growth models is extensive. The objective of our paper is to construct a model of economic growth determinants in EU countries, with focus on construction. Our model includes determinants that reflect the impact of construction on economic growth, which is the contribution to existing literature. It has been created for three groups of countries: EU28, old EU and new EU countries. We believe that this has improved the quality of the results and enabled a comparative analysis of the old and new EU countries. In order to create a model, we used a strongly balanced panel of 28 EU countries in the period 1995–2019 and employed the difference-in-differences approach. Our results for EU28 confirm positive effect of industry, gross fixed capital formation, production in construction and cost construction index on GDP, while gross wages are statistically insignificant. FDIs have low negative impact on economic growth in EU28 and old EU, but statistically insignificant in new EU countries. CO2 is significant and positively correlated with economic growth in all countries. Based on empirical results, we propose policy relevance in concluding remarks. First published online 21 October 2022